Assessing familial and social factors of life satisfaction in Pakistani transgender and non-binary individuals: implications for counseling. Issue 1 (1st February 2022) - Fatima, Shameem; Fatima, Noreen; Muazzam, Amina
Abstract: The objectives of the study were to assess the associations of family rejection and perceived social support with life satisfaction in Pakistani non-binary transgender individuals and to assess whether these associations were moderated by demographics. Results based on a sample of 105 Pakistani non-binary transgender individuals showed that family rejection was a negative predictor while social support from friends and a significant other was a positive predictor of life satisfaction. Additionally, duration of living with family independently predicted life satisfaction as well as moderated the family rejection-life satisfaction link. Implications of findings for counseling are discussed.